2020
DOI: 10.32913/mic-ict-research.v2020.n1.894
|View full text |Cite
|
Sign up to set email alerts
|

Handling Imbalanced Data in Intrusion Detection Systems using Generative Adversarial Networks

Abstract: Machine learning-based intrusion detection hasbecome more popular in the research community thanks to itscapability in discovering unknown attacks. To develop a gooddetection model for an intrusion detection system (IDS) usingmachine learning, a great number of attack and normal datasamples are required in the learning process. While normaldata can be relatively easy to collect, attack data is muchrarer and harder to gather. Subsequently, IDS datasets areoften dominated by normal data and machine learning mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…e experimental results show that GAN's balanced attack sample dataset produces more accurate results than the unbalanced attack sample set. Vu and Nguyen proposed a method based on Auxiliary Classifier Generative Adversarial Network (ACGAN) to enhance the balance of the dataset [24]. e method achieved better performance than machine learning algorithms trained on the original dataset and other sampling techniques.…”
Section: Generative Adversarial Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…e experimental results show that GAN's balanced attack sample dataset produces more accurate results than the unbalanced attack sample set. Vu and Nguyen proposed a method based on Auxiliary Classifier Generative Adversarial Network (ACGAN) to enhance the balance of the dataset [24]. e method achieved better performance than machine learning algorithms trained on the original dataset and other sampling techniques.…”
Section: Generative Adversarial Networkmentioning
confidence: 99%
“…We will compare these four methods. In addition, we also compare them with the GAN-based methods of Vu and Nguyen [24] and Lee and Park [22]. e F-measure is an overall evaluation of the Precision and Recall, which we use to measure the methods' performance.…”
Section: Experiments IIImentioning
confidence: 99%
“…Low data regimes are found in many real-life applications in which researchers face data scarcity problems [1]. The data scarcity pertains to the situation where one class is abundant in data samples (especially normal behaviour) while the anomaly samples are rare and difficult to gather [2]. The data scarcity can also be described as a data imbalance problem potentially resulting in decision bias in the machine learning (ML) classifiers.…”
Section: Introductionmentioning
confidence: 99%
“…Using generative adversarial networks (GANs) as synthetic oversamplers has been a voguish research endeavour for low data regimes [3], [7]. Various researchers have demonstrated that GANs are more effective as compared to other synthetic oversamplers like SMOTE [2], [6], [8], [9]. It is found in many studies that due to the adversarial factor, GANs can better estimate the target probability distribution [2], [8], [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation